Efficacy and safety of glucagon‐like peptide‐1 receptor agonists in type 2 diabetes: A systematic review and mixed‐treatment comparison analysis. Issue 4 (17th February 2017) - Htike, Zin Z.; Zaccardi, Francesco; Papamargaritis, Dimitris; Webb, David R.; Khunti, Kamlesh; Davies, Melanie J.
Abstract : Aims: To compare efficacy and safety of glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) in people with type 2 diabetes. Materials and methods: We electronically searched, up to June 3, 2016, published randomized clinical trials lasting between 24 and 32 weeks that compared a GLP‐1RA (albiglutide, dulaglutide, twice‐daily exenatide and once‐weekly exenatide, liraglutide, lixisenatide, semaglutide and taspoglutide) with placebo or another GLP‐1RA. Data on cardiometabolic and safety outcomes were analysed using a mixed‐treatment comparison meta‐analysis. Results: A total of 34 trials (14 464 participants) met the inclusion criteria; no published data for semaglutide were available. Compared with placebo, all GLP‐1RAs reduced glycated haemoglobin (HbA1c) and fasting plasma glucose (FPG) levels (reductions ranged from −0.55% and −0.73 mmol/L, respectively, for lixisenatide to −1.21% and −1.97 mmol/L, respectively, for dulaglutide). There were no differences within short‐acting (twice‐daily exenatide and lixisenatide) or long‐acting (albiglutide, dulaglutide, once‐weekly exenatide, liraglutide and taspoglutide) groups. Compared with twice‐daily exenatide, dulaglutide treatment was associated with the greatest HbA1c and FPG reduction (0.51% and 1.04 mmol/L, respectively), followed by liraglutide (0.45% and 0.93 mmol/L, respectively) and once‐weekly exenatide (0.38% and 0.85 mmol/L, respectively); similar reductions were found when these 3 agents were compared with lixisenatide. Compared with placebo, all GLP‐1RAs except albiglutide reduced weight and increased the risk of hypoglycaemia and gastrointestinal side effects, and all agents except dulaglutide and taspoglutide reduced systolic blood pressure. When all GLP‐1RAs were compared with each other, no clinically meaningful differences were observed in weight loss, blood pressure reduction or hypoglycaemia risk. Albiglutide had the lowest risk of nausea and diarrhoea and once‐weekly exenatide the lowest risk of vomiting. Conclusions: The RCTs in the present analysis show that all GLP‐1RAs improve glycaemic control, reduce body weight and increase the risk of adverse gastrointestinal symptoms compared with placebo. Although there were no differences when short‐acting agents were compared with each other or when long‐acting agents were compared with each other, dulaglutide, liraglutide and once‐weekly exenatide were superior to twice‐daily exenatide and lixisenatide at lowering HbA1c and FPG levels. There were no differences in hypoglycaemia between these 3 agents, whilst once‐weekly exenatide had the lowest risk of vomiting. These results, along with patient's preferences and individualized targets, should be considered when selecting a GLP‐1RA.